TRADE AND THREAT ON ORNITHOPTERA CROESUS (LEPIDOPTERA: PAPILIONIDAE), THE WALLACE’S BIRDWING BUTTERFLY IN NORTH MALUKU, INDONESIA - Djunijanti Peggie (BRIN Publishing (Penerbit BRIN), 2022)
Ornithoptera croesus, Wallace’s Golden Birdwing butterfly, is one of the most highly-demanded butterflies in the world. Annual trades of this endemic species have been monitored and mechanisms to control the trades have been developed to ensure the sustainability of the species. This paper aims to address and clarify the issues on the trade and threat to the species. The methodology involves the probe into the CITES Trade Database, into the threat to the species based on observation during field surveys, and into the possible solution. The results showed that there were some discrepancies in the data provided by the exporter and importer of the species and that the threats to the species are real. An approach to improve the condition is discussed. The solution to meet the demand for this species is offered through captive breeding and ranching for sustainable use.